Acquirer's corporate reputation in cross-border acquisitions: the moderating effect of country image. Issue 7 (16th November 2018) - Matarazzo, Michela; Lanzilli, Giulia; Resciniti, Riccardo
Abstract : Purpose: The purpose of this paper is to investigate whether, in the context of a cross-border acquisition, the acquirer's country image (CI) could moderate the relationship between the acquirer's corporate reputation (CR) and consumers' repurchase intentions towards the products of the post-acquisition target. Design/methodology/approach: The authors examined the roles played by the acquirer's CR and the acquirer's CI on consumer behaviour by considering an Italian target firm with a high reputation and comparing four foreign acquiring firms with different combinations of CR (poor/good) and CI (high/low). Findings: It was found that both CR and CI have a significant impact on Italian consumers' intention to repurchase the products of the post-acquisition target. Furthermore, the results show a greater increase in consumers' repurchase intentions when a good reputation of the acquirer is paired with a high CI for the acquirer, but a high CI cannot compensate for a poor CR. Originality/value: The research investigates, in the context of cross-border acquisitions (CBAs), the impact of the acquirer's CR and the acquirer's CI on the host country consumers' repurchase intentions after the CBA, which has not previously been thoroughly examined. It can help managers to understand the conditions under which CBAs will be favourably evaluated.